Samuelson on populist democracy, fascist capitalism, and the vicissitudes of South American economic development (1948-1997) - Boianovsky, Mauro (Center for the History of Political Economy at Duke University, 2019)
Paul Samuelson was attracted to the economic dynamics of South American countries because of the links between economic performance and political factors. He discussed the influence of “populist democracy” on Argentina's relative stagnation, which, he argued in the 1970s and early 1980s, served as a dangerous paradigm for the American economy under stagflation. Moreover, he applied his concept of
10.2139/ssrn.3481498
Keywords: Graue Literatur; Samuelson; populism; capitalist fascism; South America; economic development; inequality